KEANEKARAGAMAN PENGERTIAN YANG MELIPUTI ILMU DAN SENI - Indiana, Jaduk (Universitas Hamzanwadi, 2019)
In this journal there is the essence of diversity of notions that include science and art is a qualitative research. It is a study of a view in the field of the understanding of science and art, which has meaning and usefulness in the form of science. Understanding of science can improve understanding and functions that are systematic, orderly, organized and methodical. These problems are characterized as: 1). Presentation of understanding of knowledge that contains extensive knowledge. 2). About the difference in understanding of science and understanding of art. 3). Factors of understanding science and art towards knowledge of concepts. 4). About the number of basic understandings of art such as technical, artistic, artistic forms, and skills to make it happen, as well as content knowledge that adheres to a technical reality and artistic form. 5). About the development of art that can be done by the creation of art in order to know the form of science in the form of art. If the main problem is formulated regarding the various meanings of the form of science and the form of art includes 2 things, namely: (1). What Is the Difference of Understanding of Science and Art. And (2). What is the connection between the definition of science and art in the concept. Whereas the purpose of this research is to know clearly the background of Wujug art and art form which contains the diversity of understanding and knowledge. This research was carried out using a oriented approach from the ethnographic workings of describing diversity based on three aspects: understanding, form of art and form of art. Based on the results of this study it can be concluded that the notion of science is a method. Considering the above, it is emphasized that in art works have similarities to existence with science. Thus the essence of the work of art is also a manifestation of symbolic expressions initiated, worked on and realized using methods.